2006
DOI: 10.1073/pnas.0604225103
|View full text |Cite
|
Sign up to set email alerts
|

FLASH is an essential component of Cajal bodies

Abstract: Cajal bodies are small nuclear organelles with a number of nuclear functions. Here we show that FLICE-associated huge protein (FLASH), originally described as a component of the apoptosis signaling pathway, is mainly localized in Cajal bodies and is essential for their structure. Reduction in FLASH expression by short hairpin RNA results in disruption of the normal architecture of the Cajal body and relocalization of its components. Because the function of FLASH in the apoptosis receptor signaling pathway has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 30 publications
3
69
1
Order By: Relevance
“…We therefore conclude that FLASH is predominantly nuclear, both when transfected into cells and when endogenously expressed. Very recently Barcaroli et al (2006b) and Milovic-Holm et al (2007) published evidence supporting the same conclusion.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…We therefore conclude that FLASH is predominantly nuclear, both when transfected into cells and when endogenously expressed. Very recently Barcaroli et al (2006b) and Milovic-Holm et al (2007) published evidence supporting the same conclusion.…”
Section: Discussionmentioning
confidence: 61%
“…More likely, a partial co-localization simply reflects a dynamic association. Strong evidence for association between FLASH and Cajal bodies was recently reported by Barcaroli et al, (2006b). Association with PML nuclear bodies was also recently reported (Milovic-Holm et al, 2007).…”
Section: Discussionmentioning
confidence: 66%
“…On transcription or translation block, FLASH is rapidly degraded, whereas NPAT persists for longer (see ref. 15). Most importantly, depletion of NPAT results in a failure to enter S-phase (9), whereas down-regulation of FLASH blocks progression through S-phase (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Although FLASH was originally identified as a component of the apoptotic signaling complex known as the death-inducing signaling complex (DISC) that is assembled in response to Fas ligand binding (13,14), we have recently shown that FLASH is an essential component of CBs and is required for maintenance of their structure (15). We show that FLASH colocalizes with the histone transcriptional activator, NPAT, in CBs and is required for efficient expression of histone genes.…”
mentioning
confidence: 82%
“…More recently, FLASH was shown to localize to Cajal bodies and function in transcriptional control or RNA processing (68 -71). It is conceivable that the SBD in FLASH contributes to sumoylation-regulated assembly of nuclear complexes such as Cajal bodies or is responsible for the communication between Cajal body and sumoylated nuclear entities such as PML bodies (3,70,72).…”
Section: Volume 287 • Number 50 • December 7 2012mentioning
confidence: 99%